PENGATURAN PRAKTEK LAYANAN PROFESI ARSITEK ATAS ARSITEK ILEGAL DI PROVINSI RIAU - Hendri, Hendri; Chaniago, Rahma Evita; Shidqi, Robihtho Dhia; Ramli, Dianny Putri; Rahdiansyah, Rahdiansyah (Universitas Islam Kadiri, 2023)
The primary objective of this research is to examine the role of the architectural professional organization, namely the Indonesian Architects Association (IAI), in supervising the practices and services of the architectural profession in Riau Province. This research also aims to understand the problems related to illegal architects that occur in Riau Province and analyze the application of sanctions and solutions by IAI Riau Province to this problem. This research uses a normative juridical method which examines the implementation of positive legal provisions in each specific legal event that occurs in society, data obtained from interviews with related parties. IAI Riau has taken various efforts to supervise and develop professional architect service practice providers. This effort includes preventive and curative measures. To provide education to prospective architects regarding the applicable legal rules of the architectural profession. Apart from that, curative efforts are carried out by providing sanctions for violations of the professional code of ethics. Apart from that, IAI Riau Province also took a persuasive approach to the Provincial Government and the PUPR Service. This approach aims to align common goals and ensure that Undang-Undang No 6 of 2017 concerning architects can be fully enforced in the Riau Province Region. It is hoped that this research will provide better insight into how the regulation of architectural professional service practices can deal with the problem of illegal architects in Riau Province and optimize the role of IAI in overcoming this challenge.